Pengaruh Monensin atau Amoksisilin dalam Pakan terhadap Profil Leukosit pada Ayam Kampung Super - Nono, Daniel Robert Haba; Deta, Herlina Umbu; Datta, Frans Umbu (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2025)
The potential to develop chicken farming, especially super native chickens in Indonesia are very large because the majority of Indonesia's population is Muslim, and super native chickens also have a delicious taste and grow relatively quickly compared to other chickens. The large population of super native chickens in Indonesia and traditional rearing management can increase the risk of disease, such as coccidiosis. One option for preventing disease is through antibiotics, The antibiotics used include monensin and amoxicillin which are already on the market. This study aims to determine the difference in the appearance of blood leukocytes before and afteradministration of the antibiotics monensin and amoxicillin. There were 25 super free-range chickens sampled. Samples were taken t wice from the same super village chicken, namely before giving antibiotics and after 22 days of giving antibiotics. Data were analyzed using SPSS. Based on the results of statistical analysis using SPSS, there is an effect of adding monensin in feed and amoxicillin in drinking water on the leukocyte picture.